Characteristics of Afebrile Infants ≤60 Days of Age With Invasive Bacterial Infections - Wang, Marie E. (Hosp Pediatr, 2021)
OBJECTIVES: To describe the characteristics and outcomes of afebrile infants ≤60 days old with invasive bacterial infection (IBI). METHODS: We conducted a secondary analysis of a cross-sectional study of infants ≤60 days old with IBI presenting to the emergency departments (EDs) of 11 children’s hospitals from 2011 to 2016. We classified infants as afebrile if there was absence of a temperature ≥38°C at home, at the referring clinic, or in the ED. Bacteremia and bacterial meningitis were defined as pathogenic bacterial growth from a blood and/or cerebrospinal fluid culture. RESULTS: Of 440 infants with IBI, 78 (18%) were afebrile. Among afebrile infants, 62 (79%) had bacteremia without meningitis and 16 (20%) had bacterial meningitis (10 with concomitant bacteremia). Five infants (6%) died, all with bacteremia. The most common pathogens were Streptococcus agalactiae (35%), Escherichia coli (16%), and Staphylococcus aureus (16%). Sixty infants (77%) had an abnormal triage vital sign (temperature <36°C, heart rate ≥181 beats per minute, or respiratory rate ≥66 breaths per minute) or a physical examination abnormality (ill appearance, full or depressed fontanelle, increased work of breathing, or signs of focal infection). Forty-three infants (55%) had ≥1 of the following laboratory abnormalities: white blood cell count <5000 or >15 000 cells per μL, absolute band count >1500 cells per μl, or positive urinalysis. Presence of an abnormal vital sign, examination finding, or laboratory test result had a sensitivity of 91% (95% confidence interval 82%–96%) for IBI. CONCLUSIONS: Most afebrile young infants with an IBI had vital sign, examination, or laboratory abnormalities. Future studies should evaluate the predictive ability of these criteria in afebrile infants undergoing evaluation for IBI.